diff --git a/src/plfa/part2/Substitution.lagda.md b/src/plfa/part2/Substitution.lagda.md index 9897931c..4017c9c2 100644 --- a/src/plfa/part2/Substitution.lagda.md +++ b/src/plfa/part2/Substitution.lagda.md @@ -733,13 +733,13 @@ The proof is by induction on the term `M`. * If `x = S y`, we obtain the goal by the following equational reasoning. - exts (exts σ) (ext ρ (S y)) - ≡ rename S_ (exts σ (ρ y)) - ≡ rename S_ (rename S_ (σ (ρ y) (by the premise) - ≡ rename (ext ρ) (exts σ (S y)) (by compose-rename) - ≡ rename ((ext ρ) ∘ S_) (σ y) - ≡ rename (ext ρ) (rename S_ (σ y)) (by compose-rename) - ≡ rename (ext ρ) (exts σ (S y)) + exts (exts σ) (ext ρ (S y)) + ≡ rename S_ (exts σ (ρ y)) + ≡ rename S_ (rename S_ (σ (ρ y) (by the premise) + ≡ rename (ext ρ) (exts σ (S y)) (by compose-rename) + ≡ rename ((ext ρ) ∘ S_) (σ y) + ≡ rename (ext ρ) (rename S_ (σ y)) (by compose-rename) + ≡ rename (ext ρ) (exts σ (S y)) * If `M` is an application, we obtain the goal using the induction hypothesis for each subterm.